Design and Characterization of Dapsone Nanoemulgel for Treatment of Acne Vulgaris - Galatage, Sunil; Manjappa, Arehalli; Paratkar, Gajanan; Shaikh, Amir; Harale, Swapnil; Katkar, Rushikesh; Desai, Sujit; Kadam, Rahul; Kandukuri, Gourisankar; Pottabathula, Shyamsundar; Swami, Vishwajeet (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: Acne vulgaris is a disorder related to the skin (pilosebaceous), which is mainly caused by the formation of seborrhea, comedones, etc. It mainly affects the face, back, head and oil glands. In spite of the potent antimicrobial, anti-inflammatory and antibacterial potential of Dapsone (DPS), it has hurdles like poor water solubility and bioavailability. The objective of current research is to design, optimize and characterize Dapsone Emulgel (DPSE) for the treatment of acne vulgaris. Materials and Methods: DPSE was prepared by an oil-in-water emulsion-based method and optimized using a central composite design and the effects of carbapol-934 and liquid paraffin concentrations on drug release, viscosity and spread ability were assessed. The optimized DPSE formulation was evaluated for pH, viscosity, extrudability, spread ability, globule size, zeta potential, drug content, in vitro antibacterial assay, time-kill and film bio-adhesion assay. Results: Results revealed that the optimized DPSE exhibited a mean globule size of 382.3±4.17 nm with a PDI of 0.230.010 and a zeta potential of -21.8±3.21 mV with a drug content of 96.95±1.71% of dapsone. Optimized DPSE showed good viscosity (39481±2.645 cps), spread ability (14.68±0.02 g/cm/sec) and excellent extrudability. Optimized DPSE displayed MICs (Minimum Inhibitory Concentrations) and MBCs (Minimum Bactericidal Concentrations) of 10±1.5 μg/mL and 21±2 μg/mL, respectively, against P. acne when compared to S. aureus. (MIC-54±2.5 μg/mL MBC-98±4 μg/mL). Furthermore, DPSE inhibited biofilm formation and bacterial adhesion in a dose-dependent manner, with 100% inhibition obtained in 48 hr at MBC. The percentage of live bacteria in the biofilm treated with MBC and the MIC concentration of DPSE was 31.54±1.32% and 62.91±3.12%, respectively, in comparison to the control's 100%. Conclusion: From the results, we conclude that optimized DPSE can be used as a competent alternative to a current treatment for effective management of acne vulgaris. However, further in vivo studies are required to establish its efficacy in the treatment of acne vulgaris.
Keywords: Acne vulgaris; Dapsone; Emulgel; Zeta Potential; Antibacterial assay; P. acne etc